Cell Permeable Peptides Containing “Cycloalanine” Residues - Wu, Hao (Angew Chem Int Ed Engl, 2016)
We present here an efficient alternative to the N-methylation for the purpose of morphing protein-binding peptides into more serum stable and cell permeable compounds. This involves the incorporation of a ”cycloalanine (CyAla)” into a peptide in a way that avoids difficult coupling steps. We demonstrate the utility of this chemistry in creating a cell permeable derivative of a high affinity HIV Rev protein-binding peptide.